Assessment and mitigation of the fire vulnerability and risk in the historic city centre of Aveiro, Portugal - Silva, Dener (2022)
Identifying fire risk in urban centres is instrumental for supporting informed decision-making and outlining efficient vulnerability mitigation strategies. Historic centres are particularly complex in this regard due to the high density of combustible materials in these areas, the favourable fire propagation conditions between buildings, and the complex urban morphology, which makes the evacuation of inhabitants difficult in case of a fire emergency. Recent safety regulations tend not to be fully applicable to historic city centres, where the specificities of the buildings, together with the need to safeguard their heritage value, make the rules for new buildings incompatible. For that reason, an adaptation of current evaluation methods is required to assure the safety of these places. The present paper aims to contribute to this topic by presenting and discussing the results obtained from the application of a simplified fire risk assessment methodology to a representative part of the historic city centre of Aveiro, Portugal. Data were collected through fieldwork building inspections and the results were mapped using a Geographic Information System tool. The study reveals that around 63% of the assessed buildings have a level of fire risk greater than the level of risk which is acceptable for buildings with this type of use and value. Based on the work developed, different mitigation strategies are suggested and compared. Finally, the results obtained in this work are compared with results published for historic urban areas with similar characteristics.